Shape conditions and phonological context - Asudeh, Ash; Klein, Ewan (Proceedings of the 8th International Conference on Head-Driven Phrase Structure Grammar, 2002)
This paper builds on Zwicky's (1986) notion of shape condition, that is, a rule that specifies the phonological shape of inflected forms "by reference to triggers at least some of which lie outside the syntactic word". Zwicky observes that "many rules traditionally classified as external sandhi rules are [shape conditions]". They are not phonological rules in the usual sense, since they only apply to specific lexical items and are active within syntactic rather than phonological domains. Shape conditions are problematic in many standard grammar architectures. On the one hand, they seem to be constraints on lexical entries, while on the other hand, they make reference to the syntactic context. Hayes (1990) has sketched a theory of "precompiled phrasal phonology" in which allomorph choice is conditioned by subcategorization frames in lexical entries. However, his approach is not formalized in any detail, and moreover makes the implicit claim that the relation between a shape condition target and its triggers can be equated with the syntactic relation between a lexical head and its complement. Although this assumption holds good for the Hausa phenomena he addresses, we do not believe that it holds in general. HPSG appears to offer promising framework for formalizing something like Hayes' approach, but the standard machinery also makes it hard to distinguish a shape condition trigger from a complement. In order to overcome this difficulty, we develop the notion of phonological context: a feature of signs which allows us to condition allomorphic alternation in terms of (i) the phonological edges, and (ii) the syntactic properties of an expression's immediate syntactic sisters. We show how our analysis deals with four illustrative cases: the indefinite article alternation in English, syncretic liaison forms for possessive pronouns in French, Hausa verb-final vowel shortening, and soft mutation in Welsh nouns.